Multi-epitope vaccine design for hepatitis E virus based on protein ORF2 and ORF3 - Lu, Qiong; Wu, Hao; Meng, Jing; Wang, Jiangyuan; Wu, Jiajing; Liu, Shuo; Tong, Jincheng; Nie, Jianhui; Huang, Weijin (Frontiers in Microbiology, 2024)
Hepatitis E virus (HEV), with heightened virulence in immunocompromised individuals and pregnant women, is a pervasive threat in developing countries. A globaly available vaccine against HEV is currently lacking. Here, we designed a multi-epitope vaccine based on surface proteins ORF2 and ORF3 of HEV using immunoinformatics. The vaccine comprised 23 nontoxic, nonallergenic, soluble peptides. The stability of the docked peptide vaccine-TLR3 complex was validated by molecular dynamic simulations. The induction of effective cellular and humoral immune responses by the multipeptide vaccine was verified by simulated immunization. Taken together, these findings provide a foundation for future HEV vaccine studies.